Nucleolar Cycle and Its Correlation with Chromatoid Bodies in the Tilapia rendalli (Teleostei, Cichlidae) Spermatogenesis - Peruquetti, Rita Luiza [UNESP]; Taboga, Sebastiao Roberto [UNESP]; Vilela de Azeredo-Oliveira, Maria Tercilia [UNESP] (Wiley-liss, 2010)
The aim of this study was: (1) to monitor the nucleolar material distribution using cytological and cytochemical techniques and ultrastructural analysis; and (2) to compare the nucleolar material distribution with the formation of the chromatoid body (CB) in the germ epithelium of Tilapia rendalli. Nucleolar fragmentation occurred during the leptotene of prophase I and nucleolus reorganization occurred in the early spermatid nucleus. The area of the early spermatid nucleolus was significantly smaller than that of the spermatogonia nucleolus. Ultrastructural analysis showed an accumulation of nuages, which form the CB, before nucleolar fragmentation in the spermatogonia cytoplasm. The CB was observed in association with mitochondrial clusters in the cytoplasm of primary spermatocytes, as well as in those of initial and later spermatids. In conclusion, the nucleolus seems to be related to CB formation during spermatogenesis of T rendalli, because at the moment of nucleolus fragmentation in the primary spermatocytes, the CB reaches its largest area and it is able to complete important functions during spermatogenesis. The reorganized nucleolus of the initial spermatids has a lower area due several factors, one of which is the probable migration of nucleolar fragments from the nucleus to the cytoplasm, therefore playing a role in CB formation. Anat Rec, 293:900-910, 2010. (C) 2010 Wiley-Liss, Inc.
Keywords: Nucleolus; Nucleolar cycle; Chromatoid body; Reproduction; Spermatogenesis; Fish